The degradation of poloxamer 188 in buffered formulation conditions - Wei Chen; Siegfried Stolz; Vincent Wegbecher; Dixy Parakkattel; Christina Haeuser; Nuria Sancho Oltra; Ravuri S. K. Kishore; Steven Bond; Christian Bell; Robert Kopf (SpringerOpen, 2022)
Abstract Poloxamer 188 (P188) as a non-ionic surfactant is used in proteinaceous formulations to prevent protein adsorption to hydrophobic surfaces and unfolding at interfaces, preventing the formation of aggregates and particles. Its chemical intactness is crucial to the stability of drug products due to its protecting effects at interfaces. In order to identify and mitigate potential risks that might cause the degradation of P188 during the manufacturing process and storage, in the current work, the stability of P188 was investigated by forced degradation in buffered formulation conditions via oxidation and thermal stress conditions. The process of degradation was monitored through the dedicated liquid adsorption chromatography (LAC) with high sensitivity, and the degradants were characterized by high-resolution mass spectrometry. Results suggest that the vulnerability of P188 is largely related to the buffer conditions. Histidine promotes degradation in the presence of hydroxyl radicals but inhibits the degradation in the presence of H2O2 and alkyl radicals. In thermal stress conditions, histidine protects P188 from degradation at 40 °C, and activates its decay only at higher temperature, like 60 °C.